Conclusion: Paradise Lost - Christy Davis (Symphony in the Flint Hills, 2018)
Introduction: The first white men to see the Texas Hill Country described it as a paradise. The tall grass “stretched as far as the eye could see, covering valleys and hillsides alike” with random trees “rising out of a rippling pale green sea."